INSTAGRAMMERS’ PERCEPTION OF USING INSTAGRAM APPLICATION FOR LEARNING ENGLISH VOCABULARY - Fitri, Allina Kurnia; Maghfiroh, Ana (Sanata Dharma University Yogyakarta, 2024)
In this generation, the use of Instagram as a learning media for learning English is quite familiar. This research determined the Instagrammers' perceptions of using the Instagram application for learning English vocabulary. The data were analyzed using a descriptive qualitative methodology, and some earlier research was used to support the findings. The study examined Instagram users who used the platform to practice their English vocabulary. To get precise information about how 35 respondents felt about using Instagram applications to acquire English vocabulary, interviews with 5 informants were conducted. The majority of respondents to the study were satisfied with using the Instagram app to develop English vocabulary, according to the study's findings. Instagram users concurred that the platform aids in their vocabulary development. Instagram users can choose the vocabulary topic they want to focus on improving with an Instagram video or photo, and they agree that Instagram makes it simple for them to recall new English words.